The Role of Institutional Design and Enabling Environmental: Collaborative Governance of a Pilgrimage Tourism, Indonesia - Musleh, Moh.; Subianto, Agus; Tamrin, M. Husni; Bustami, Mohammad Reevany (Universitas Muhammadiyah Malang, 2023)
This article discusses the role of stakeholders from the descendants of Kings, who collaborated with the government and private sectors in managing of the pilgrimage tourism heritage site of the tomb of the Kings of Asta Tinggi, in Sumenep district. The purpose of this study was to investigate the various factors that influence stakeholder collaborations in the management of sustainable pilgrimage tourism and which stakeholder groups have a sustained traditional of authority. This qualitative research uses a case study approach and data collection through in-depth unstructured interviews and observations. This study seeks to take a new perspective in the analysis of the collaborative governance theory in the face of the social environment factor. The study results show that stakeholders, facilitative leadership, and enabling environmental factors become resources and strengths in the success of collaborative governance even though the role of private and government sectors are still limited. The findings reveal that stakeholders from the community, namely the traditional group as a companion of pilgrims, have an important role in collaboration, because they can only be replaced by the descendants, while the collaborative initiation comes from the community. We suggest the importance of government initiation to expand collaboration networks and facilitate the formation of the institutional administrator of Asta Tinggi site, through reconciliation which represents two descendants of Kings. The findings of this study are expected to enrich the theory of collaborative governance.